Explore autophagy-related lncRNA-miRNA-mRNA ceRNA networks for diagnosis of early-onset schizophrenia through transcriptome analysis - Hu, Wei; Du, Xinzhe; Wang, Xinxia; Zhang, Kexin; Li, Junxia; Gao, Yao; An, Ting; Zhang, Hong; Zhang, Yu; Ren, Zhiyong; Xu, Yong; Liu, Sha (Frontiers in Psychiatry, 2025)
BackgroundThe severe functional impairment and poor prognosis of early-onset schizophrenia (EOS) create a great need to identify effective biomarkers for early diagnosis in young psychiatric patients. Current research indicates a potential link between loss of autophagy function and emotional and behavioral abnormalities in individuals with psychiatric disorders.Materials and MethodsThis study aimed to explore diagnostic autophagy-related endogenous competitive RNA (ceRNA) networks for EOS patients. The messenger RNAs (mRNAs) and long non-coding RNAs (lncRNAs) expression profiles were obtained from peripheral blood mononuclear cells of 18 EOS patients and 12 healthy controls (HC). A co-expression analysis was performed between 365 core lncRNAs and 55 differentially expressed autophagy-related genes (ARGs) to identify differentially expressed autophagy-related lncRNAs. Subsequently, five diagnostic autophagy-related lncRNAs were identified as candidate genes to construct a ceRNA regulatory network using least absolute shrinkage and selection operator (LASSO) Cox regression, and receiver operating characteristic (ROC) curve analysis was performed to evaluate their predictive accuracy. Then, putative interactions among lncRNA-microRNAs (miRNAs)-mRNA were determined based on the lncRNASNP2 and TarBase databases.ResultsThree lncRNAs, twenty miRNAs, and ten mRNAs were selected to construct an autophagy-associated ceRNA network associated with EOS occurrence. Through protein-protein interaction network analysis, five hub mRNAs were identified, which exhibited good predictive ability in distinguishing EOS patients from healthy individuals. ROC curve analysis demonstrated that integrating three diagnostic lncRNAs (RP1-135L22.1, RP5-884C9.2, RP11-390F4.3) along with five hub mRNAs (EIF4G1, AKT1, BAX, WIPI2, MAPT) appeared to yield better diagnostic accuracy compared to using either lncRNAs or mRNAs alone. Furthermore, all three diagnostic lncRNAs and five hub mRNAs were positively correlated with at least two types of immune infiltration.ConclusionThrough transcriptome analysis, we searched for diagnostic autophagy-related ceRNA networks, which provided valuable candidates for the early diagnosis of EOS.